Effects of probiotics on the prevention and treatment of children with allergic rhinitis: a meta-analysis of randomized controlled trials - Luo, Xinyi; Wang, Huan; Liu, Huixia; Chen, Yue; Tian, Li; Ji, Qing; Xie, Dengpiao (Frontiers in Pediatrics, 2024)
Recent studies have demonstrated the anti-allergic effects of probiotics in humans. However, their role in preventing and treating pediatric allergic rhinitis has not been thoroughly investigated. This study aimed to systematically review the efficacy and preventive effects of probiotics on pediatric allergic rhinitis.We systematically searched PubMed, Embase, the Cochrane Central Register of Controlled Trials, and Web of Science databases for all relevant studies on probiotics and pediatric allergic rhinitis. Studies meeting the inclusion criteria were included, data were extracted, and metaanalyses were performed.Results: A total of 28 studies with 4765 participants were included in this study. The pooled resultsshowed that the use of probiotics was associated with a significant improvement in total nose symptom scores (SMD, -2.27; 95% CI, -3.26 to -1.29; P < 0.00001), itchy nose scores (SMD, -0.44; 95% CI, -0.80 to -0.07; P = 0.02), sneezing scores (SMD, -0.47; 95% CI, -0.84 to -0.10; P = 0.01), eye symptoms (SMD, -3.77; 95% CI, -5.47 to -2.07; P < 0.00001), and Pediatric Rhinoconjunctivitis Quality of Life Questionnaire (SMD, -2.52; 95% CI, -4.12 to -0.92; P < 00001).However, the use of probiotics was not associated with the incidence of allergic rhinitis (RR, 0.9; 95% CI, 0.74-1.08; P = 0.26).The present study demonstrated that probiotics were effective and safe for improving pediatric allergic rhinitis symptoms and quality of life. However, probiotics could not prevent pediatric allergic rhinitis.